STUDI PENURUNAN BESI (Fe) DAN MANGAN (Mn) DALAM AIR TANAH DENGAN MENGGUNAKAN CLAY FILTER - Khairul Amri; Ganjar Samudro; Irawan Wisnu Wardhana (Jurnal Teknik Lingkungan, 2013)
The use of groundwater as a source of fresh water to the people would become a problem when it contains of Fe and Mn. This happens because in the ground water there is no directly contact with the air outside and the weathering of rocks, so that Fe and Mn in the ground water is still soluble. Meanwhile the amount of Fe and Mn in the ground is never the same in every location. This case could be some impacts to people’s kidney health. In this study, content of Fe and Mn in the ground water will be reduced by using Clay filter media. This study uses 3 wells water samples character with different level of Fe and Mn in sample A is 0.001 mg / l Fe, 0.16 mg / l Mn, sample is B 0.019 mg / l Fe, 0.05 mg / l Mn, and sample C is 3,242 mg / l Fe, 0.27 mg / l Mn. The height level of water influence to the Clay filter becomes the consideration in this study, they are 50 cm, 100 cm and 150 cm. Clay Filter is operated for 12 hours continuously with taking the reuslt of filtration sampling per 2 hours. Based on the research, this study finds the operating time to decrease the concentration of Fe and Mn with Clay Filter optimally from the three height levels in all kinds of different water samples and its categorization has reached 100% at the fourth hours.